Laparoscopic Cholecystectomy: An Experience in Combined Military Hospital, Rangpur (Journal of Rangpur Medical College, 2025)
Background: Laparoscopic surgery (LC) has gained popularity quickly due to its many benefits over traditional open surgery. The reduction in postoperative pain had a positive impact on humans, as did the shorter hospital stay and earlier return to work. Nevertheless, this procedure has various per-operative and postoperative complications that cannot be ignored, despite being a minimally invasive technique. Objective: The aim was to evaluate the intraoperative, postoperative complications of laparoscopic cholecystectomy (LC); the rate of conversion to open cholecystectomy and the reasons for it; the length of the hospital stay following the procedure; and the operating time. Methods: This retrospective study included 245 individuals who had laparoscopic cholecystectomy performed between July 2022 and June 2024 at Department of Surgery,Combined Military Hospital (CMH), Rangpur. Retrospective analysis was done on patient medical records. Armed Forces persons and their family members who are entitled to have medical treatment facilities were included in this study. Results: Out of 245 participants, 211 (86.12%) were females and 34 (13.88%) males.The average age of the male and female patients was 40.13 and 39.20 years respectively.Most prevalent age group was between 3rd and 4th decade in both sexes. Hypertension (HTN) (6.12%), diabetes mellitus (DM) (6.12%) and HTN and DM together (6.12%) were most commonly associated comorbidities. 180 (73.47%) patients showed normal anatomy of gall bladder (GB) per-operatively. 39 (15.92 %) patients had major and minor intra operative complications while 14 (5.71%) patients had postoperative complications. 12 (4.90%) conversion open cholecystectomy was done in that series due to different reasons. In 126 cases (51.53%) operating was 40 minutes and in most cases (86.12%) post operative hospital stay was